Implementasi Teori Hudud Menurut Pemikiran Muhammad Syahrur terhadap Upaya Pencegahan Tindak Pidana Korupsi di Indonesia - Faizah, Dian Dwi Alifatul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2018)
This article discusses the Implementation of Hudud Theory According to Muhammad Syahrur's Thought on Corruption Prevention Efforts in Indonesia. The theft of state money or commonly referred to as corruption according to Syahrur can be subjected to a maximum sentence of the opposite hand cut, the cross, exile or life imprisonment and the death penalty which is annihilated by hirabah. The Syahrur Hudud theory can be applied as a legal alternative for perpetrators of corruption in an effort to prevent corruption in Indonesia. The Shahrur Theory has similarities in the law that apply to corruptors in Indonesia, namely in Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. In the law, the death penalty is set as the maximum sentence for perpetrators of corruption in Indonesia. The death penalty is one of the maximum punishments that exist in the theory of Muhammad Syahrur's hud?d relating to criminal acts of corruption which are analogous to the hirabah. In addition, imprisonment and fines as minimum penalties for corruptors also have similarities within the minimum limits of the theory, namely repenting and returning all corrupted assets accompanied by fines. And prison is a place of seclusion that is expected to make the offender deterrent and repent and not repeat his actions.